FXR activation prevents the development of vascular calcification in ApoE(−/−) mice with chronic kidney disease - Miyazaki-Anzai, Shinobu (2010)
RATIONALE: Vascular calcification is highly associated with cardiovascular morbidity and mortality, especially in patients with chronic kidney disease. The nuclear receptor farnesoid X receptor (FXR) has been implicated in the control of lipid, carbohydrate and bile acid metabolism in several cell types. Although recent studies have shown that FXR is also expressed in vascular smooth muscle cells, its physiological role in vasculature tissue remains obscure. OBJECTIVE: Here, we have examined the role of FXR in vascular calcification. METHODS AND RESULTS: The FXR gene, a bile acid nuclear receptor, was highly induced during osteogenic differentiation of bovine calcifying vascular cells (CVC) and in the aorta of apolipoprotein E (ApoE)(−/−) mice with chronic kidney disease which are common tissue culture and mouse model, respectively, for aortic calcification. FXR activation by a synthetic FXR agonist, 6α-ethyl chenodeoxycholic acid (INT-747) inhibited phosphate induced-mineralization and triglyceride accumulation in CVC. FXR dominant negative expression augmented mineralization of CVC and blocked the anti-calcific effect of INT-747 whereas VP16FXR that is a constitutively active form reduced mineralization of CVC. INT-747 treatment also increased phosphorylated c-Jun N-terminal kinase (JNK). SP600125 (specific JNK inhibitor) significantly induced mineralization of CVC and ALP expression, suggesting that the anti-calcific effect of INT-747 is due to JNK activation. We also found that INT-747 ameliorates chronic kidney disease (CKD) induced-vascular calcification in 5/6 nephrectomized ApoE(−/−) mice without affecting the development of atherosclerosis. CONCLUSIONS: These observations provide direct evidence for that FXR is a key signaling component in regulation of vascular osteogenic differentiation and, thus representing a promising target for the treatment of vascular calcification.